Robust and Partially Adaptive Estimation of Regression Models - Butler, Richard J.; McDonald, James B.; Nelson, Ray D.; White, Steven B. (The Review of Economics and Statistics, 1990)
Richard J. Butler, James B. McDonald, Ray D. Nelson, Steven B. White, Robust and Partially Adaptive Estimation of Regression Models, The Review of Economics and Statistics, Vol. 72, No. 2 (May, 1990), pp. 321-327